2003
DOI: 10.1080/02724980244000369
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Effects in Word Naming: Evidence from English and Japanese Kanji

Abstract: Three experiments investigated whether reading aloud is affected by a semantic variable, imageability. The first two experiments used English, and the third experiment used Japanese Kanji as a way of testing the generality of the findings across orthographies. The results replicated the earlier findings that readers were slower and more error prone in reading low-frequency exception words when they were low in imageability than when they were high in imageability (Strain, Patterson, & Seidenberg, 1995). This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
67
2
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(82 citation statements)
references
References 56 publications
9
67
2
4
Order By: Relevance
“…A final observation concerns the high correlation between familiarity and imageability. This finding, however, is not particularly surprising, given that the two variables are thought to be reliable indexes of semantic code activation (Cuetos & Barbon, 2006;Shibahara et al, 2003).…”
Section: Resultscontrasting
confidence: 39%
See 1 more Smart Citation
“…A final observation concerns the high correlation between familiarity and imageability. This finding, however, is not particularly surprising, given that the two variables are thought to be reliable indexes of semantic code activation (Cuetos & Barbon, 2006;Shibahara et al, 2003).…”
Section: Resultscontrasting
confidence: 39%
“…Imageability corresponds to the ease with which a mental image can be generated in response to the presentation of a written word. Imageability is thought to index semantic richness and is often used to investigate the activation of semantic codes in lexical-processing tasks (e.g., Cortese, Simpson, & Woolsey, 1997;Cuetos & Barbon, 2006;Shibahara, Zorzi, Hill, Wydell, & Butterworth, 2003;Strain, Patterson, & Seidenberg, 1995. As is described below, we followed the same procedure as Paivio, Yuille, and Madigan (1968) to collect the norms for the picture names.…”
Section: The Russian Languagementioning
confidence: 99%
“…In particular, whereas the effects are obtained in the lexical decision task, they are typically absent in reading aloud. In reviewing the literature, Shibahara, Zorzi, Hill, Wydell, and Butterworth (2003) suggested that, so far, only imageability has been shown to have an effect on reading latencies (e.g., Strain et al, 1995). However, imageability seems low in the case of complex numerals, so an effect of this factor was not to be expected in our experiments.…”
Section: Discussionmentioning
confidence: 59%
“…Other variables, such as initial phoneme of a syllable, age of acquisition, homophone density, and phonological frequency, have only recently been examined and shown to be important (Chen, Wang, Wang, & Peng, 2004;Liu, Zhang, & Shu, 2006;Ziegler, Tan, Perry, & Montant, 2000). Finally, semantic-level variables such as imageability and concreteness have also recently been found to be important in the processing of Japanese Kanji (Chinese characters; Shibahara, Zorzi, Hill, Wydell, & Butterworth, 2003), as well as in word naming and lexical decision in Chinese (Chen & Peng, 1998; see also Q. Zhang & Zhang, 1997).…”
mentioning
confidence: 99%